2019
DOI: 10.5130/ajceb.v19i1.6574
|View full text |Cite
|
Sign up to set email alerts
|

Green site practices and environmental performance: how project complexity moderates the relationship

Abstract: The characteristics of a project that makes it hard to understand, predict, and manage its general behavior despite the availability of required information relating to the project dynamics is referred to as project complexity. A good knowledge of project complexity at the construction phase of a project, as well as a well thought out plan to manage complexity will determine how proficiently construction projects are planned, managed, and executed in an environmentally friendly manner. The level of complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…The signi cant positive effect of GCPs on CS observed in this study can be attributed to the monetary and non-monetary bene ts associated with the adoption of GCPs such as better project quality and greater productivity of construction workers (Karakhan & Gambatese, 2017). It has been reported that the non-adoption of GCPs could result in nes been imposed on the client, and could eventually lead to sealing off of the project site (Onubi et al, 2019), thus leading to extra cost and schedule overruns.…”
Section: Discussion Of Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The signi cant positive effect of GCPs on CS observed in this study can be attributed to the monetary and non-monetary bene ts associated with the adoption of GCPs such as better project quality and greater productivity of construction workers (Karakhan & Gambatese, 2017). It has been reported that the non-adoption of GCPs could result in nes been imposed on the client, and could eventually lead to sealing off of the project site (Onubi et al, 2019), thus leading to extra cost and schedule overruns.…”
Section: Discussion Of Resultsmentioning
confidence: 65%
“…Even though the number of clients accepting to adopt GCPs has been on the increase, their choice to adopt these practices is passive, since they are been compelled by the government to do so (Shan et al, 2020). This could lead to a situation whereby they may not be satis ed as they ought to be when such practices are been adopted on their projects due to cost overrun, delays, increase in complexity, and risks (Onubi et al, 2019).…”
Section: Green Construction Practices and Client Satisfactionmentioning
confidence: 99%
“…The moderator effect of project complexity has been used on project performances such as new product development, environmental performance, crowdfunding performance, and performance of international development projects [54][55][56][57]. The authors used project complexity as a moderator to the correlation between project events and project performance.…”
Section: Project Complexity As a Moderatormentioning
confidence: 99%
“…The performance of construction projects is largely dependent on the approach adopted in carrying out various site activities (Forster, 2014; Onubi et al , 2019b). It requires foresight and well thought out choice of construction practices and operations to guarantee the optimal performance of the construction project (Ajayi et al , 2017).…”
Section: Introductionmentioning
confidence: 99%